Influence of Third Party Fund, Financing, and CAR on Profitability with NPF mediation in Islamic Banks - Agustin, Eka Dinda (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
The merger of Bank Syariah Mandiri, BNI Syariah, and BRI Syariah into Bank Syariah Indonesia (BSI) IN 2021 marked a new phase in the development of Islamic banking in Indonesia. This consolidation successfully increased total assets, capital strength, and third-party funds (DPK). However, the rise in funding and capital has not consistently been followed by an increase in profitability (ROA), partly due to the increasing level of non-performing financing (NPF). This study aims to analyze the direct and indirect effects of Third Party Fund (DPK), Financing, and Capital Adequacy Ratio (CAR) on profitability (ROA), with Non- Performing Financing (NPF) as a mediating variable. This research uses a quantitative associative approach with secondary data from the financial reports of Islamic Commercial Bank in Indonesia for the period 2021 – 2024. The data will be analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine direct effects and mediation relationships. The findings of this study are expected to provide empirical evidence regarding whether NPF mediates the relationship between funding, financing, capital, and profitability. The study is also expected to offer theoretical, practical, and policy implications for Islamic banking performance improvement in Indonesia